R-ChIP for genome-wide mapping of R-loops by using catalytically inactive RNASEH1 - Chen, Jia-Yu; Zhang, Xuan; Fu, Xiang-Dong; Chen, Liang (Nature protocols, 2019)
Nascent RNA may form a three-stranded structure with DNA, called an R-loop, which has been linked to fundamental biological processes such as transcription, replication and genome instability. Here, we provide a detailed protocol for a newly developed strategy, named R-ChIP, for robust capture of R-loops genome-wide. Distinct from R-loop-mapping methods based on the monoclonal antibody S9.6, which recognizes RNA-DNA hybrid structures, R-ChIP involves expression of an exogenous catalytically inactive RNASEH1 in cells to bind RNA-DNA hybrids but not resolve them. This is followed by chromatin immunoprecipitation (ChIP) of the tagged RNASEH1 and construction of a strand-specific library for deep sequencing. It takes ~3 weeks to establish a stable cell line expressing the mutant enzyme and 5 more days to proceed with the R-ChIP protocol. In principle, R-ChIP is applicable to both cell lines and animals, as long as the catalytically inactive RNASEH1 can be expressed to study the dynamics of R-loop formation and resolution, as well as its impact on the functionality of the genome. In our recent studies with R-ChIP, we showed an intimate spatiotemporal relationship between R-loops and RNA polymerase II pausing/pause release, as well as linking augmented R-loop formation to DNA damage response induced by driver mutations of key splicing factors associated with myelodysplastic syndrome (MDS).